"Look It, This is how You Know:" Family Forest Walks as a Context for Knowledge-Building About the Natural World. Issue 2 (3rd April 2018) - Marin, Ananda; Bang, Megan
ABSTRACT: This case study focuses on a Native American family's experience on a walk in an urban forest preserve. Drawing on interaction analysis traditions, we analyze video data and transcript data to characterize how learning unfolds in place, in this case an urban forest. We build on this analysis, as well as the work of Indigenous scholars, to theoretically develop walking, reading, and storying land as a methodology for making sense of physical and biological worlds.